Molecular ontology of the parabrachial nucleus. Issue 10 (21st February 2022) - Karthik, Samyukta; Huang, Dake; Delgado, Yaritza; Laing, Justin J.; Peltekian, Lila; Iverson, Gabrielle N.; Grady, Fillan; Miller, Rebecca L.; McCann, Corey M.; Fritzsch, Bernd; Iskusnykh, Igor Y.; Chizhikov, Victor V.; et al.
Abstract: Diverse neurons in the parabrachial nucleus (PB) communicate with widespread brain regions. Despite evidence linking them to a variety of homeostatic functions, it remains difficult to determine which PB neurons influence which functions because their subpopulations intermingle extensively. An improved framework for identifying these intermingled subpopulations would help advance our understanding of neural circuit functions linked to this region. Here, we present the foundation of a developmental‐genetic ontology that classifies PB neurons based on their intrinsic, molecular features. By combining transcription factor labeling with Cre fate‐mapping, we find that the PB is a blend of two, developmentally distinct macropopulations of glutamatergic neurons. Neurons in the first macropopulation express Lmx1b (and, to a lesser extent, Lmx1a ) and are mutually exclusive with those in a second macropopulation, which derive from precursors expressing Atoh1 . This second, Atoh1 ‐derived macropopulation includes many Foxp2 ‐expressing neurons, but Foxp2 also identifies a subset of Lmx1b ‐expressing neurons in the Kölliker–Fuse nucleus (KF) and a population of GABAergic neurons ventrolateral to the PB ("caudal KF"). Immediately ventral to the PB, Phox2b ‐expressing glutamatergic neurons (some coexpressing Lmx1b ) occupy the KF, supratrigeminal nucleus, and reticular formation. We show that this molecular framework organizes subsidiary patterns of adult gene expression (including Satb2, Calca, Grp, and Pdyn ) and predicts output projections to the amygdala ( Lmx1b ), hypothalamus ( Atoh1 ), and hindbrain ( Phox2b / Lmx1b ). Using this molecular ontology to organize, interpret, and communicate PB‐related information could accelerate the translation of experimental findings from animal models to human patients. Abstract : The parabrachial nucleus (PB) contains diverse, intermingled neurons regulating various homeostatic functions. Their neuronal distributions often do not align with cytoarchitectural subdivisions. Here, we show that the PB is a blend of two, developmentally distinct glutamatergic populations identified by the embryonic transcription factors Atoh1 and Lmx1a / Lmx1b . We show that macropopulation identity predicts output connectivity and other gene expression patterns in this region. Our findings lay the foundation for a molecular ontology that will be useful for interpreting transcriptomic, connectomic, and other experimental data involving PB neurons.